Informed Hypothetico‐Deductive Reasoning Based on Clinical Signs for Diagnosis of Equine Laminitis Using Decision Tree Analysis. (September 2015) - Wylie, C.E.; Shaw, D.J.; Verheyen, K.L.P.; Newton, J.R.
Abstract : Reasons for performing study: Effective diagnosis of equine laminitis is necessary to allow prompt instigation of palliative and therapeutic treatments, yet there has been limited work regarding diagnostic accuracy. Objectives: To compare the prevalence of clinical signs in laminitis and non‐laminitis lamenesses to evaluate the capabilities of discrimination for differential diagnosis. Study design: Analytical epidemiological study. Methods: Veterinary practitioners completed a pre‐designed checklist of laminitis‐associated clinical signs identified by literature review, for equine lameness of any origin. A case was defined as a horse/pony with veterinary‐diagnosed, clinically apparent laminitis, attended by a participating practitioner. Associations between clinical signs and case/control status were tested by logistic regression with adjusted odds ratios and 95% confidence intervals, with veterinary practice as a fixed effect, and Wald P‐value calculated. Multivariable analysis using graphical classification tree‐based statistical models allowed comprehension of the prevalence in the data associated with particular clusters of clinical signs. Results: Data were collected for 588 laminitis cases and 201 non‐laminitis lamenesses. The overall prevalence of specific clinical signs ranged from 2.7% for 'sole prolapse' to 85.0% for 'lame at trot'. Differences in prevalence ranged from −14.1% for 'lame at trot' (more common in controls) to +71.9% for 'short stilted gait at walk' (more common in cases). Five clinical signs had a difference in prevalence of greater than +50%: 'reluctance to walk', 'short, stilted gait at walk', 'difficulty turning', 'shifting weight' and 'increased digital pulse'. Bilateral forelimb lameness was the best discriminator (92% of animals with this clinical sign had laminitis). The additional presence of increased digital pulses improved this to 99%. Flat/convex sole, shifting weight and short stilted gait at walk were also useful discriminators. Conclusions: This is the first study to provide information aiding diagnostic hypothetico‐deductive reasoning based on clinical signs to differentially diagnose laminitis from other lamenesses. Ethical animal research:  Ethical approval obtained from Royal Veterinary College. Owners gave informed consent for their horses' inclusion in the study.Sources of funding:  Project funded by World Horse Welfare. C.E. Wylie currently funded by The Margaret Giffen Charitable Trust.Competing interests:  None declared.